2008
DOI: 10.1016/j.fct.2008.09.063
|View full text |Cite
|
Sign up to set email alerts
|

Phototoxicity of phenylenediamine hair dye chemicals in Salmonella typhimurium TA102 and human skin keratinocytes

Abstract: Phenylenediamines (PD) are dye precursors used to manufacture hair dyes. The three PDs, 1,2-, 1,3-, and 1,4-PD and three chlorinated PDs, 4-chloro-1,2-PD, 4-chloro-1,3-PD, and 4,5-dichloro-1,2-PD were studied for their mutagenic effect in Salmonella typhimurium TA 102, cytotoxicity in human skin keratinocyte cells, and for DNA cleavage. The results show that all six compounds are not toxic/ mutagenic in TA 102 bacteria or skin cells, and do not cause DNA cleavage in ΦX 174 phage DNA. If the same tests are carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…To the best our knowledge, no previous studies showing considerable toxicity of our identified FMD compounds have been reported in the literature. A previous study by Yu et al (2008) showed that all six non-halogenated and halogenated (chlorinated) phenylenediamines (PD) as dye precursors used to manufacture hair dyes are not toxic/mutagenic in Salmonella typhimurium TA 102 bacteria or skin keratinocyte cells, and do not cause DNA cleavage in ΦX 174 phage DNA. Their phototoxicity test in skin cells showed that without light irradiation, all the PD compounds are not toxic to the keratinocytes up to 1000 μM; only at an extremely high PD concentration (1000 μM) and with extensive exposure to light irradiation (at a large light dose of 3.3 J/cm 2 of UVA and 6.3 J/cm 2 of visible light), two chlorinated PDs and two non-chlorinated PDs show modest phototoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…To the best our knowledge, no previous studies showing considerable toxicity of our identified FMD compounds have been reported in the literature. A previous study by Yu et al (2008) showed that all six non-halogenated and halogenated (chlorinated) phenylenediamines (PD) as dye precursors used to manufacture hair dyes are not toxic/mutagenic in Salmonella typhimurium TA 102 bacteria or skin keratinocyte cells, and do not cause DNA cleavage in ΦX 174 phage DNA. Their phototoxicity test in skin cells showed that without light irradiation, all the PD compounds are not toxic to the keratinocytes up to 1000 μM; only at an extremely high PD concentration (1000 μM) and with extensive exposure to light irradiation (at a large light dose of 3.3 J/cm 2 of UVA and 6.3 J/cm 2 of visible light), two chlorinated PDs and two non-chlorinated PDs show modest phototoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…). However, this same compound was reported to be not cytotoxic to keratinocytes up to 1000 μM in the absence of light (Mosley‐Foreman et al, ). Even in the presence of light, it was found to be cytotoxic to this epidermal cell type only at high concentration (1000 μM).…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have proved that hair dyes can penetrate the skin [23]. When applied to the skin, the combination of light irradiation and contamination with hair dye ingredients may cause adverse effects on human health [24]. Hair dyes have been proven to be photosensitive for a long period of time [24].…”
Section: Photocytotoxicity Of Hair Dyesmentioning
confidence: 99%